Economic growth and income inequality: Evidence from Thailand - Paravee Maneejuk (2018)
© Springer International Publishing AG 2016. Evidence from this study shows a significant relationship between growth and income inequality in which inequality creates a negative impact on the growth, but the impact of economic growth on income inequality is nonlinear. This result captures the Kuznets Hypothesis, finding the level of growth that can reduce unequal distribution of income in Thailand. Finally, this study also discovers a certain level of inflation that can help reduce income inequality effectively.